Some New Inequalities Involving κ-Fractional Integral for Certain Classes of Functions and Their Applications. (29th April 2020) - Zhou, Shuang-Shuang; Rashid, Saima; Dragomir, Silvestru Sever; Latif, Muhammad Amer; Akdemir, Ahmet Ocak; Liu, Jia-Bao
Abstract : In this article, we present several new inequalities involving the κ -fractional integral for the integrable function ℱ which satisfies one of the following conditions: a ℱ q is preinvex for some q > 1 ; b ℱ ′ is bounded; c ℱ ′ is a Lipschitz function. As applications, we establish new inequalities for the weighted arithmetic and generalized logarithmic means.